Missing-Self Triggers NK-Mediated Microvascular Injuries and Chronic Rejection of Allogenic Kidney Transplants. (July 2018) - Koenig, Alice; Chen, Chien-Chia; Marçais, Antoine; Mathias, Virginie; Sicard, Antoine; Rabeyrin, Maud; Racapé, Maud; Duong, Jean Paul; Bruneval, Patrick; Dussurgey, Sébastien; Ducreux, Stéphanie; Morelon, Emmanuel; et al.
Abstract : Background: Natural Killer cells (NK) are effectors of the innate immune system carrying inhibitory KIR, which regulate the killing function of these cells by interacting with MHC class I molecules (MHC-I). The "missing-self" hypothesis proposes that NK can sense the absence of self MHC-I on the surface of allogeneic cells. This unique characteristic suggests that NK could promote innate-driven rejection, a concept that has not been validated in clinical transplantation. Methods and Results: 938 kidney transplant recipients had a graft biopsy between 2004 and 2012 in our center. Among them, 130 had microvascular inflammation (mvi, g+ptc Banff score ≥ 2), which is usually attributed to humoral rejection. Nevertheless, only 75 had circulating donor-specific antibodies (DSA) directed against HLA antigens or endothelial cells susceptible to explain their microvascular inflammation. We hypothesize that "missing-self" could be responsible for the lesions of the 55 remaining patients (mvi+DSA-). Finally, DNA samples were available for 44 pairs. A matched control group of 55 patients with no microvascular inflammation and no DSA was constructed (mvi-DSA-). Recipients' KIR genes and donors' and recipients' HLA ligands were genotyped and the licensing of the 5 inhibitory KIR with known MHC-I ligands (KIR2DL1/C2, KIR2DL2/C1, KIR2DL3/C1, KIR3DL1/Bw4, KIR3DL2/A3, A11) was assessed for both groups. The proportion of patients with at least 1 licensed inhibitory KIR-ligand mismatch was higher in mvi+DSA- group (66% vs 38%, p=0.009). In a human in vitro model, we demonstrated that the lack of self MHC-I on endothelial cells can activate NK. This activation triggers mTOR pathway in NK, which can be blocked by rapamycine. Using a murine in vivo cellular model of missing-self mediated killing, we found that rapamycine (but not CNI) can prevent the killing of targets. Finally, we confirmed the existence of missing-self induced rejection in a murine heart transplantation model and its sensitivity to mTOR inhibition. Conclusion: "Missing-self" triggers NK-mediated chronic vascular rejection of allogeneic kidneys. MTOR inhibitors might be of interest to prevent this previously unrecognized type of rejection.